Studi Sinergitas Perguruan Tinggi Kepariwisataan Dan Dinas Pariwisata Kabupaten Pangkep Di Provinsi Sulawesi Selatan (Jurnal Ilmiah Pariwisata, 2016)
The Ministry of Tourism of Indonesia has been supervising four tourism higher schools (with two additional tourism higher schools) to produce human resources in the tourism and hospitality industry. For this reason, there should be good synergy between the tourism higher school and the regional board of tourism particularly if they are located in the same destination. Nevertheless, there is no empirical data concerning how the regional board of tourism and the tourism higher school collaborate in developing the regional tourism. This research aims at examining the partnership between the regional government and the tourism educational institution as well as proposing recommendation in strengthening synergy between the two institutions. By implementing qualitative research in April 2016 through interviews to staffs in the Tourism Board of Pangkep Regency of South Sulawesi and the Tourism Polytechnic of Makassar, this research reveals that partnership has been implemented by Bandung Tourism Institute and the Tourism Board of Pangkep Regency.This fact arises question on the role of Makassar Tourism Polytechnic in building synergy with the regional government particularly in the eastern part of Indonesia. Thus, it is recommended that partnership should be strengthened through formal and informal tourism activities guided by the Tourism Polytechnic of Makassar. Education and training in tourism for staff is required to support the partnership
Keywords: Synergy, Partnership, Tourism Polytechnic of Makassar, The Regional Board of Tourism of Pangkep Regency